Amalan jagaan diri pesakit diabetes mellitus jenis 2 di pusat diabetes Hospital Universiti Sains Malaysia (HUSM) - Kasmaliza, Mohd (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
A quantitative, descriptive and cross sectional study was conducted to detennine the level of self care and relationship between self care and blood glucose level among type 2 diabetes mellitus patients. One hundred and thirteen type 2 diabetic patients who get the treatment from Pusat Diabetes Hospital Universiti Sains Malaysia were involved in this study. All the patients were selected into the study by using the convenience sampling technique. The self care elements are measured by using the instrument which been modified from Yan Su (2005) questionnaire that based on Orem's theory. The instrument is divided into 2 parts which include demographic items and self care questionnaire. This research's questionnaire are been validated by three experts who had experience in medical area, Orem' s theory and also who has experience in management of type 2 diabetes mellitus patients. The data was analyze by using 'Statistical Package Social Science (SPSS)' version 12.0. Reliability test for this research was done and the alpha value was 0. 731. There are five dimensions in self care which include dimension of seeking appropriate medical assistance, dimension of being aware and monitoring blood glucose level and the effect of medication, dimension of compliance on taking hyperglycemic drug, dimension of accepting yourself and required treatment of diabetes mellitus and dimension of learning to live with diagnose of type 2 diabetes mellitus patient. This result show that self care among type 2 diabetes mellitus patients was applied in moderate level. Pearson correlation was used to determine the correlation between self care and blood glucose level among type 2 diabetes mellitus patients. The result show that the correlation was weak with r value was -0.183. Self care give non significant correlation with blood glucose level with p value is 0.053. From the result, hypothesis of this research show that self care is not associated with blood glucose level. A good and continuous self care is important in order to make sure that blood glucose level and can prevent more severe complication to the patients with type 2 diabetes mellitus.